Analisis Data Pasien Klinik Halim Untuk Menentukan Masa Menopouse Menggunakan Metode Teorema Bayes - Melfiyanti Wau; Ahmad Zakir; Septiana Dewi Andriana (Unit Pengelola Jurnal Universitas Harapan Medan, 2022)
Abstract Menopause is a transitional period from mentruation to no longer having menstruation. Women who have enteredmenopause are likely to experience a deterioration in health, especially physical changes. Hot flushes, vaginasbecoming dry, sagging skin and wrinkles are examples of physical changes. The physical changes caused bymenopause can affect the psychological condition of menopausal women such as irritability, anxiety, stress anddepression. The problem of uncertainty of knowledge in this expert system is solved using the method of Bayes' Theorem. The process of determining the diagnosis in this expert system begins with a consultation session, wherethe system will ask relevant questions to the patient according to the main symptoms of monopause diseaseexperienced by the patient. Bayes' theorem is used to calculate the probability of an event occurring based on theinfluence obtained from the results of observations. In addition to this bayes theorem method makes use of sampledata obtained from the population also takes into account an initial distribution called the prior distribution. Thefinal result of this study is an expert system for diagnosing monopause diseases along with the probability valueof the diagnosed disease, which shows the level of system confidence in the disease and the therapeutic advice thatshould be given.